2013
DOI: 10.1111/1742-6723.12076
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure cuffs as a vector for transmission of multi‐resistant organisms: Colonisation rates and effects of disinfection

Abstract: Although MRSA and VRE were infrequently isolated, current disinfection and infection control protocols need to be improved given the greater recovery of organisms from the inner compared with outer surfaces of BP cuffs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
2
8
1
3
Order By: Relevance
“…Conversely, by using non-disposable cuffs and demonstrating the efficacy of decontamination the importance of safety could be enhanced while the environmental impact (and cost) are minimised. Previous findings elsewhere, utilising the same contamination categories as demonstrated with this present study (Grewal et al, 2013), have found that ED sphygmomanometer cuffs were more likely to be severely contaminated, having > 100 cfu present. Comparatively our findings indicate the majority (68.1%) of the cuffs to be minimally contaminated with ⩽ 10 cfu.…”
Section: Discussionsupporting
confidence: 82%
“…Conversely, by using non-disposable cuffs and demonstrating the efficacy of decontamination the importance of safety could be enhanced while the environmental impact (and cost) are minimised. Previous findings elsewhere, utilising the same contamination categories as demonstrated with this present study (Grewal et al, 2013), have found that ED sphygmomanometer cuffs were more likely to be severely contaminated, having > 100 cfu present. Comparatively our findings indicate the majority (68.1%) of the cuffs to be minimally contaminated with ⩽ 10 cfu.…”
Section: Discussionsupporting
confidence: 82%
“…Sixteen percent of our BP cuffs were contaminated by virulent bacteria: MRSA (6.7%), Enterococcus faecalis (6.7%), and Staphylococcus lugdunensis (3.3%, Table 1). Other authors have found virulent bacteria on BP cuffs; these included MSSA (up to 33% [1,12,13]), MRSA (up to 31% [1,8,13,14]), Clostridium difficile (10% to 33% [2,13]), and vancomycin-resistant enterococci (up to 18% [3,4]). During the investigation of nosocomial outbreaks, several studies have found genetic links between bacteria from infected patients and cultures from BP cuffs for S. aureus [1,5], VRE [3,4], Pseudomonas aeruginosa , and Serratia marcesens [1].…”
Section: Discussionmentioning
confidence: 99%
“…Desta maneira, evita-se a transmissão de possíveis infecções nosocomiais, uma vez que as superfícies próximas ao paciente e/ou aquelas mais tocadas podem ser contaminadas por microrganismos de importância epidemiológica. [6][7][8][9] De acordo com as informações recebidas pela Comissão de Controle de Infecção Hospitalar (CCIH) do hospital, não houve registros de casos de IRAS causadas pelos microrganismos encontrados no presente estudo, no período próximo a realização da coleta. O que não descarta a importância de conscientizar a equipe multiprofissional em realizar a lavagem das mãos de maneira correta e realizar regularmente a higienização das ferramentas de trabalho que entram em contato direto ou indiretamente com o paciente internado.…”
Section: Discussionunclassified
“…O que não descarta a importância de conscientizar a equipe multiprofissional em realizar a lavagem das mãos de maneira correta e realizar regularmente a higienização das ferramentas de trabalho que entram em contato direto ou indiretamente com o paciente internado. [6][7][8][9][10][11]24 Neste hospital, as técnicas de assepsia são realizadas de acordo com as normas preconizadas pela CCIH, devendo a desinfecção dos materiais acontecer uma vez ao dia e após alta ou óbito do paciente, utilizando álcool 70%. Um estudo realizado no Rio de Janeiro comprovou que o uso de álcool gel mostrou-se adequado quando usado na desinfecção de estetoscópios contaminados por cepas MRSA, onde a redução da contaminação por microrganismos foi de 71,44%, confirmando a importân-cia da realização das rotinas de assepsia.…”
Section: Discussionunclassified
See 1 more Smart Citation